1984
DOI: 10.1038/307066a0
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal chromaffin cells form functional cholinergic synapses in culture

Abstract: Adrenomedullary cells and autonomic ganglion cells originate from the neural crest. Both cell types synthesize, store and release catecholamines; however, their structural and functional properties are distinctly different. Aloe and Levi-Montalcini have shown in vivo that when the adrenal medulla is exposed to exogenous nerve growth factor (NGF) most cells differentiate into neuronal cells substantially similar to sympathetic neurones. Experiments in vitro have also shown that neonatal as well as adult adrenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(19 citation statements)
references
References 12 publications
1
17
0
1
Order By: Relevance
“…For example, synaptic vesicles have been found in many non-neuronal cells including pinealocytes [120], chromaffin [121,122] and pancreatic beta cells [123]. Receptors for the excitatory neurotransmitter glutamate have also been found in non-neuronal cells including retinal pigment epithelial [124], urinary bladder epithelial, prostate epithelial cells [125] as well as osteoblasts [126-129].…”
Section: Discussionmentioning
confidence: 99%
“…For example, synaptic vesicles have been found in many non-neuronal cells including pinealocytes [120], chromaffin [121,122] and pancreatic beta cells [123]. Receptors for the excitatory neurotransmitter glutamate have also been found in non-neuronal cells including retinal pigment epithelial [124], urinary bladder epithelial, prostate epithelial cells [125] as well as osteoblasts [126-129].…”
Section: Discussionmentioning
confidence: 99%
“…They were cultured and treated with 2.5S nerve growth factor (NGF, 50 ng/ml, Alomone Labs Ltd., Jerusalem, Israel) to induce differentiation into neuronal cells (Ogawa et al, 1984). Human umbilical vein endothelial cells (HUVEC) were purchased from Cambrex (Walkersville, MD, USA).…”
Section: Cellsmentioning
confidence: 99%
“…5A), an adrenal medullary pheochromocytoma tumor line (Greene and Tischler 1976) that has many properties of a committed adrenergic precursor and which responds to NGF with neurite outgrowth. This induction is also observed in primary cultures of dissociated neonatal adrenal chromaffin cells exposed to NGE In situ hybridization to adrenal chromaffin cell cultures in the presence of NGF revealed that those cells that converted to a neuronal morphology (Unsicker et al 1978;Naujoks et al 1982;Ogawa et al 1984;Doupe et al 1985a) also expressed SCG10 mRNA at high levels (Fig. 6A,B).…”
Section: Regulated Expression Of Scg10mentioning
confidence: 78%